Extra-Judicial Killing in the Perspective of Islamic Criminal Law - Said Reza Pahlevi; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2025)
Extra-judicial killing or extrajudicial killings outside legal procedures has become a phenomenon that causes controversy in the realm of law, ethics, and human rights because these actions are carried out without a legitimate judicial mechanism. This practice raises a dilemma between the interests of public security and the protection of individual rights. This study aims to analyze the legitimacy, social and moral impact, and comparison of Islamic criminal law norms with contemporary practices related to extra-judicial killing. The research uses a normative or normative juridical approach by analyzing primary sources in the form of the Qur'an, Hadith, classical fiqh, and the principles of maqashid al-sharia, as well as secondary sources in the form of academic literature, journals, and national regulations related to the taking of life and law enforcement. The analysis was carried out descriptively-analytically and comparatively to assess the suitability of empirical practices with sharia norms. The results of the study show that Islamic criminal law places human life as a fundamental right that can only be taken through formal procedures such as qisas and diyat with court supervision, so that unilateral actions by the authorities have no legal legitimacy and give rise to moral and spiritual responsibilities. The social impact of this practice includes psychological trauma of victims and families, public distrust of the authorities, social instability, and the potential for the emergence of a culture of violence. A comparison of Islamic legal norms with contemporary practices highlights the tension between public security and the principle of justice, where sharia norms emphasize accountability, transparency, and protection of individual rights. In conclusion, fair and ethical legal procedures in accordance with the principles of maqashid al-sharia are important instruments to prevent extra-judicial killings, maintain social stability, and strengthen the legitimacy and morality of law enforcement officials.